(untitled) (Fiep Bulletin - online, 2013)
For a significant portion of young people, school activities are the only opportunities to develop physical activity and significant schools show good results in its promotion interventions. To assess the prevalence of overweight, obesity and cardiac risk of high school students in the city of QUEIMADAS-PB. Methods: A descriptive, exploratory qualitative approach random field, school-based, was conducted between April and May 2012 in the State School for Elementary and High School Ernesto Francisco do Rego City QUEIMADAS-PB were evaluated in with anthropometric measurements, height, weight and waist and hip circumference, for testing the body mass index (IMC), waist circumference (CA) and waist-hip ratio (R.C/Q). The sample consisted of 50 subjects aged 15 to 17 years of both genders, from a universe of 200 students, drawn randomly. For Prevalence of Overweight and Obesity, Cardiac Risk I and II, and Metabolic Complications. The prevalence was higher among females with 36% (18 subjects). While the prevalence in males was lower with 14% (7 subjects). But there was an indication of malnutrition of 12% (6 subjects), and is considered a representative value of health risk. The school sets up an opportunity to approach and approach of children and adolescents to insert knowledge and habits that promote healthy lifestyle and active, especially through school physical education curriculum. For a significant proportion of young people, school activities are the only opportunities to develop physical activity significantly, contributing to the culture of body movement, decreased sedentary lifestyle and weight